Plasma seminal suíno na criopreservação de sêmen ovino - Martins, Kauê Rodriguez (2014)
There is a growing interest in using artificial insemination (AI) in sheep due to the potential for genetic improvement. However, cryopreservation damages spermatozoa, decreasing their fertilizing potential when frozen semen is deposited in the cervix. Sperm damages attributed to cryopreservation may be minimized by the addition of seminal plasma (SP), which contains several factors produced by the testis, epididhymis and accessory glands with potential to prevent premature capacitation. Supplementation of SP prior to freezing would be beneficial for various processes of periods of the selection and freezing process, reported before freezing would be beneficial for the processes of selection and freezing. The supplementation of extenders with SP from ram and boars is associated with increased sperm motility after incubation in vitro, as well as when used for cooling, freezing and thawing. The objectives of this study were to test the addition of 20% boar SP to the extender to freeze ram sperm and to evaluate parameters of sperm quality after thawing. Ejaculates from four rams and three boars were collected to form pooled SP samples. A fraction of each pooled sample was used for protein quantification. Six samples from four rams were collected and diluted in Tris-egg yolk - glycerol for freezing, forming three treatments: control (no SP); inclusion of 20% ram SP; and inclusion of 20% boar SP. After thawing, the samples were subjected to a thermal stress test for five hours. Sperm quality was assessed every two hours. Analyses by flow cytometry were done to evaluate the integrity of acrosome and membrane integrity. For the control, ram SP and boar SP treatments, the evaluated parameters of sperm quality were: motility (30.4 ± 2.0, 24.6 ± 2.0 and 30.0 ± 2.0, respectively); membrane integrity (37.5 ± 2.6; 40.9 ± 2.6 and 31.4 ± 2.6 respectively); mitochondrial functionality (70.0 ± 1.7; 61.8 ± 1.7 and 63.6 ± 1.7); and DNA integrity (91.2 ± 3.1; 96 5 ± 3.1 and 93.6 ± 3.1 respectively). For those parameters, no significant differences were observed across treataments (P > 0.05). However, addition of boar SP to the extenders was related to greater acrosome integrity (59, 3 ± 3.5) than that of the control (46.7 ± 3.5) (P < 0.05), although both means were similar (P > 0.05) to that observed for the treatment with ram SP (56.7 ± 3.5). Despite of the benefit on acrosome integrity related to addition of boar SP, no other positive effects were observed for post-thawing ram sperm viability.